2009
DOI: 10.1007/s10695-009-9325-7
|View full text |Cite
|
Sign up to set email alerts
|

Sperm quality in male Barbus barbus L. fed different diets during the spawning season

Abstract: Sperm quality of Barbus barbus L. was compared among the three following dietary regimes: Group A, fed 100% commercial diet (Karpico containing 33% crude protein and 6% fat), Group B, fed 78% commercial diet and 22% frozen chironomid (Chironomus plumosus) larvae, and Group C, fed 56% commercial diet and 44% frozen chironomid larvae. Concentrations of polyunsaturated fatty acids (PUFAs) in Group A, B, and C were 39.1, 42.0, and 44.6, respectively, as a percentage of total fatty acids. Sperm morphology, volume, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 38 publications
2
20
1
1
Order By: Relevance
“…The effect of nutrition in barbel males on the sperm quality was described by Alavi et al (2008cAlavi et al ( , 2009a. However, there is no information about female and male fecundity and its changes under controlled conditions during the reproductive season.…”
Section: Growth and Survival Rates Puberty And Fecundity In Captive mentioning
confidence: 96%
“…The effect of nutrition in barbel males on the sperm quality was described by Alavi et al (2008cAlavi et al ( , 2009a. However, there is no information about female and male fecundity and its changes under controlled conditions during the reproductive season.…”
Section: Growth and Survival Rates Puberty And Fecundity In Captive mentioning
confidence: 96%
“…[19]). In addition to several examples on the adverse consequences of low food quantity and/or quality on postcopulatory sexual traits across a wide range of taxa [20,21], precopulatory sexual traits can also be negatively affected. In particular, the expression of conspicuous sexually selected male colour traits depends on food quantity and/or quality (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this idea, when food quantity or quality is low, total sperm length often decreases (Alavi et al 2009;) whereas within-individual variation in sperm morphology increases (Hellriegel and Blanckenhorn 2002). However, other studies found no relationship between condition and sperm length (Gage and Cook 1994;Amitin and Pitnick 2007;Gasparini et al 2013).…”
Section: Condition Dependence Of Ejaculate Traitsmentioning
confidence: 89%
“…Limited resources may result in trade-offs within ejaculates, such as, a trade-off between sperm size and sperm number (Immler et al 2011). Empirically, sperm count (Gasparini et al 2013;Kaldun and Otti 2016;Chapter 4), sperm length (Simmons and Kotiaho 2002;Alavi et al 2009;; Chapter 4), and within-male variation (Chapter 4) are associated with body condition in a wide range of taxa. However, there are very few studies that have assessed the condition dependence of the individual morphological components of the cell, which could indicate areas of the cell that are energetically expensive, potentially due to sexual selection.…”
Section: Causes For Intraspecific and Population-level Variation In Smentioning
confidence: 99%